Spider-girl. Vol. 4 Turning point - DeFalco, Tom.; Olliffe, Pat.; Williamson, Al 1931-.; Buscema, Sal.; Frenz, Ron. (New York Marvel Comics, 2005)
The adventures of Spider-Man's daughter continue as Mayday once again faces Kaine, Spider-Man swings again, and Darkdevil is... actually nice?! Plus: Meet new heroes and villains, take a peek into the fantasies of Mayday's friends, and witness the return of the Green Goblin!
"Contains material originally published in magazine form as Spider-Girl #17-21and #1/2'"--P. [2 of cover]
UCWS-2789g donated by Tristan Manalastas - January 2016
Keywords: Spider-Girl (Series).; Women heroes -- Comic books, strips, etc. -- Fiction; Graphic novels; Comic books, strips, etc; CHR 2005.